2014
DOI: 10.1155/2014/651872
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Circulating Follicular Helper T Cells in Children with Hand, Foot, and Mouth Disease Caused by Enterovirus 71 Infection

Abstract: Enterovirus 71 (EV71) is a major causative agent of hand, foot, and mouth disease (HFMD) in children. The role of T follicular helper (TFH) cells in EV71-infected children remains unclear in regulating humoral immunity. The frequency of circulating ICOShigh/PD-1highCXCR5+CD4+ TFH cells in the children with mild and severe EV71 infection and healthy controls (HC) was detected by flow cytometry, respectively. IL-21 and IL-6 mRNA expression and their serum levels, Bcl-6 mRNA expression, and specific neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
2
20
1
1
Order By: Relevance
“…In this study, correlation analysis showed an increase in the plasma levels of IL-17A and the frequencies of cTh17 cells, which also implied that the increased IL-17A expressions might be predominantly produced by cTh17 cells and associated with the pathogenesis of EV71-associated HFMD. Moreover, plasma levels of TNF-α, IL-6 and IL-23 cytokines were significantly higher in the EV71-associated HFMD patients than in HC, particularly in the severe patients, which was consistent with previous reports [4, 29, 30]. These findings indicated that increased plasma levels of cytokines (TNF-α, IL-6 and IL-23) possibly could explain the increased percentages of cTh22 and cTh17 cells and plasma levels of IL-22 and IL-17A in patients with EV71-associated HFMD, particularly in the severe patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, correlation analysis showed an increase in the plasma levels of IL-17A and the frequencies of cTh17 cells, which also implied that the increased IL-17A expressions might be predominantly produced by cTh17 cells and associated with the pathogenesis of EV71-associated HFMD. Moreover, plasma levels of TNF-α, IL-6 and IL-23 cytokines were significantly higher in the EV71-associated HFMD patients than in HC, particularly in the severe patients, which was consistent with previous reports [4, 29, 30]. These findings indicated that increased plasma levels of cytokines (TNF-α, IL-6 and IL-23) possibly could explain the increased percentages of cTh22 and cTh17 cells and plasma levels of IL-22 and IL-17A in patients with EV71-associated HFMD, particularly in the severe patients.…”
Section: Discussionsupporting
confidence: 93%
“…Mild cases were defined by typical clinical features and spontaneously recovered within one week. Severe cases were usually defined in accordance with previous reports [4, 26]. Clinical data and specimens were collected from the patients with EV71-associated HFMD., and Ppatients were excluded if they were also infected by bacteria before treatment, but specimens were.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that cellular immunity, rather than humoral immunity, is associated with the clinical outcomes of EV-A71 infection (43). In addition, previous reports have shown that the number of circulating immune cells, including T follicular helper cells, type 1 helper and cytotoxic T cells, and T helper 17 and 22 cells, increases with the severity of HFMD after EV-A71 infection, accompanied by an increase in the secretion of various cytokines, such as IL-6, IL-17, IL-21, IL-22, and TNF-␣ (44)(45)(46). In another report, a decrease in the number of CD4 ϩ and CD8 ϩ T cells and NK cells was observed when the patients advanced from autonomic nervous system dysregulation to pulmonary edema (27), suggesting that cellular immunity is one of the factors that governs disease severity.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, increasing evidence has shown that cytotoxic CD8+T cells contribute to platelet destruction 36 . It is well known that TFH cells play pivotal roles in autoimmune diseases and virus infection 13 , 37 - 39 . However, the role of TFH cells remains unclear in the development and progression of ITP.…”
Section: Discussionmentioning
confidence: 99%